Polyvinyl Alcohol Food Packaging System Comprising Green Synthesized Silver Nanoparticles - Ahmed Elsayed Abdelhamid; Eman AboBakr Ali Yousif; Manal Mohamed Talaat El-Saidi; Ahmed Ali El-Sayed (Indonesian Journal of Chemistry, 2021)
Green synthesis of silver nanoparticles (AgNPs) using aqueous Moringa extract and their incorporation in polyvinyl alcohol (PVA) as food packaging materials have been performed. The prepared nanoparticles were characterized via Ultraviolet-visible spectra and transmission electron microscope, and the results revealed the formation of silver nanoparticles in a semi-spherical shape with an average size ranged from 2 to 5 nm. The addition of different ratios of the nanoparticles onto the PVA matrix and their crosslinking via citric acid to obtain nanocomposite sheets were performed. The nanocomposite sheets were characterized using FT-IR, UV-Vis, and TGA. In addition, their mechanical properties were evaluated. Water vapor permeability rate and water content were also determined. The composite sheets showed good thermal and optical performance. Antibacterial activities of the prepared nanocomposite sheets were evaluated, and the results exhibited good resistance to bacterial growth.